2020
DOI: 10.3390/polym12061256
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic Substrates Based on Crosslinker-Free Poly(ε-Caprolactone):Poly(2-Hydroxyethyl Methacrylate) Semi-Interpenetrated Networks Promote Serum Protein Adsorption

Abstract: A simple procedure has been developed to synthesize uncrosslinked soluble poly(hydroxyethyl methacrylate) (PHEMA) gels, ready for use in a subsequent fabrication stage. The presence of 75 wt % methanol (MetOH) or dimethylformamide (DMF) impedes lateral hydroxyl–hydroxyl hydrogen bonds between PHEMA macromers to form during their solution polymerization at 60 °C, up to 24 h. These gels remain soluble when properly stored in closed containers under cold conditions and, when needed, yield by solvent evaporation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As shown in Figure 5a, although there is no cross-linking agent in 30H-NOX-3D, there are a physical cross-linking based on hydrogen bonds from the terminal hydroxyl groups of pHEMA and a subsequent entanglement between pHEMA polymer chains. [34] These polymer chains entanglements can act as mobile cross-links for energy dissipation, [35] which contribute to the high fracture strain of 30H-NOX-3D hydrogel. Furthermore, the hydrogen bonds between the hydroxyl groups on pHEMA polymer chains are considered as the weakest intermolecular interactions, [35][36] therefore, a low tensile strength and modulus are found for the 30H-NOX-3D hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5a, although there is no cross-linking agent in 30H-NOX-3D, there are a physical cross-linking based on hydrogen bonds from the terminal hydroxyl groups of pHEMA and a subsequent entanglement between pHEMA polymer chains. [34] These polymer chains entanglements can act as mobile cross-links for energy dissipation, [35] which contribute to the high fracture strain of 30H-NOX-3D hydrogel. Furthermore, the hydrogen bonds between the hydroxyl groups on pHEMA polymer chains are considered as the weakest intermolecular interactions, [35][36] therefore, a low tensile strength and modulus are found for the 30H-NOX-3D hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…For example, polymer B's peak water absorbance was 28–29 at room temperature, while it was only 22–23 at 40 °C after 72 h. It was reported that poly(2‐hydroxyethyl methacrylate) (PHEMA) had the hydrophobicity of its backbone. [ 27 ] Prins and co‐workers observed that the PHEMA gel's swelling in water decreased from 30 to 50 °C. [ 27 ] Jhon and co‐workers reported the decreased permeability of electrolytes in uncross‐linked PHEMA membrane from 5 to 15 °C due to decreased water content in the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] Prins and co‐workers observed that the PHEMA gel's swelling in water decreased from 30 to 50 °C. [ 27 ] Jhon and co‐workers reported the decreased permeability of electrolytes in uncross‐linked PHEMA membrane from 5 to 15 °C due to decreased water content in the membrane. [ 28 ] Water absorbance results from this study suggest that the beads’ hydrophobicity from HEMA units’ backbone in the copolymers increased from room temperature to 40 °C.…”
Section: Resultsmentioning
confidence: 99%